The Gendered Revolution in Writing: The Story of the First Prose Masterpiece in Western Civilization. - Blackmer, Corinne (2000)
Keywords: dept.eng; faculty_collection; sabbatical_report

Self-Portrait - Johnson, Brian (Edition key satch(el) ; v. 1, no. 3, 2000)
Keywords: dept.eng; faculty_collection

Red Stick Men: Stories - Parrish, Tim (University Press of Mississippi, 2000)
The characters in these stories "are always on the verge of disasters that emanate from the hard living they endure in the city they call 'Red Stick,'" i.e., Baton Rouge, Louisiana.--Jacket.
Keywords: Baton Rouge; Fiction; Fiction; Baton Rouge (La.); Louisiana; Oil industry workers; Social life and customs; dept.eng; faculty_collection

Fair Haven - Shipley, Vivian (Negative Capability Press, 2000)
Keywords: dept.eng; faculty_collection

Postmodernism and the politics of “culture” - Katz, A. (Postmodernism and the Politics of "Culture", 2000)
Postmodernism and the Politics of ‘Culture’ is a comparative critical analysis of the political and intellectual ambitions of postmodernist critical theory and the academic discipline of cultural studies. Katz’s polemical aim is to show that cultural studies comes up short in both areas, because its practitioners focus on too-narrow issues-primarily, celebrating the folkways of micro-communities-while denying the very possibility of studying, understanding, and changing society in any comprehensive way and to any universally beneficial purpose. He argues that scholars and activists alike would do well to make use of the analytical tools of postmodernist critical theory, whose practitioners acknowledge the political significance of the differences between social groups, but do not consider them to be unbridgeable, and so seek to develop a set of practices for creating a truly inclusive, truly democratic public sphere. © 2000 Taylor & Francis. All rights reserved.
Keywords: dept.eng